2019
DOI: 10.15171/npj.2019.16
|View full text |Cite
|
Sign up to set email alerts
|

Factor V Leiden and prothrombin G20210A mutations and risk of vaso-occlusive complications in sickle cell disease: A meta-analysis through the lens of nephrology

Abstract: Hemolysis is a fundamental feature that contributes to hypercoagulability and thrombotic complications in sickle cell disease (SCD). Factor V Leiden (FVL) and prothrombin G20210A mutations are the most common genetic thrombophilia. Objectives: The aim of this meta-analysis is to determine the relationship between FVL or prothrombin G20210A and susceptibility of vaso-occlusive complications (VOC) in SCD. Patients and Methods: For this meta-analysis, eligible studies were retrieved via two systematic searches pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…21,22 A Meta-analysis showed that mutant genotypes (GA+AA vs. GG) of the FVL mutation was found to be higher in SCD patients with vasocculsion crises than in SCD patients without it revealed that FVL mutation as a high-risk factor for VOC in SCD patients). 23 Our study showed positive heterozygous prothrombin G 20210 A Figure 8 in 18.0% of SCD patients versus complete absence in controls (0%), (Table 2) and this agree with a study showed a significant prevalence of heterozygous PRT G20210A mutation among patients (10.93%) 21 and other study Heterozygous prothrombin G20210A mutation was (5.08%) in SS patients (allele A frequency 2.54%) and in controls (5.08%). 24 Meta-analysis showed that the distribution of prothrombin G20210A mutation in SCD patients with or without vasocculsion is similar and revealed that the prothrombin G20210A is not associated with the risk of VOC in SCD patients 14 Other studies reported completely absence of prothrombin mutation and no significant associations between the SCA and prothrombin G20210A mutation.…”
Section: Discussionsupporting
confidence: 91%
“…21,22 A Meta-analysis showed that mutant genotypes (GA+AA vs. GG) of the FVL mutation was found to be higher in SCD patients with vasocculsion crises than in SCD patients without it revealed that FVL mutation as a high-risk factor for VOC in SCD patients). 23 Our study showed positive heterozygous prothrombin G 20210 A Figure 8 in 18.0% of SCD patients versus complete absence in controls (0%), (Table 2) and this agree with a study showed a significant prevalence of heterozygous PRT G20210A mutation among patients (10.93%) 21 and other study Heterozygous prothrombin G20210A mutation was (5.08%) in SS patients (allele A frequency 2.54%) and in controls (5.08%). 24 Meta-analysis showed that the distribution of prothrombin G20210A mutation in SCD patients with or without vasocculsion is similar and revealed that the prothrombin G20210A is not associated with the risk of VOC in SCD patients 14 Other studies reported completely absence of prothrombin mutation and no significant associations between the SCA and prothrombin G20210A mutation.…”
Section: Discussionsupporting
confidence: 91%
“…4 Several lines of evidence demonstrate that the genetic factors involved in inflammation, cell-cell interaction, and nitric oxide biology could influence the severity of SCA. [5][6][7] Fetal hemoglobin (HbF) is one of the normal hemoglobin variants and a predominant hemoglobin during the fetal stage. HbF exists at approximately 90 to 95% during birth and gradually drops to <2% by the age of 1 year.…”
Section: Introductionmentioning
confidence: 99%
“…4 Several lines of evidence demonstrate that the genetic factors involved in inflammation, cell–cell interaction, and nitric oxide biology could influence the severity of SCA. 5 6 7…”
Section: Introductionmentioning
confidence: 99%